Realization of a 30-W highly efficient and linear reconfigurable dual-band power amplifier using the continuous mode approach. Issue 2 (April 2014) - Carrubba, Vincenzo; Maroldt, Stephan; Mußer, Markus; Walcher, Herbert; Van Raay, Friedbert; Quay, Rüdiger; Ambacher, Oliver; Wiegner, Dirk; Seyfried, Ulrich; Bohn, Thomas; Pascht, Andreas
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents the design methodology and the realization of a highly linear and power-efficient reconfigurable dual-band amplifier based on the continuous/Class-ABJ approach. The Class-ABJ theory allows presenting different reactive solutions on both fundamental and second harmonic terminations compared with the standard Class-AB mode. Despite the various terminations, a constant optimum output performance in terms of power, gain, and efficiency can still be achieved. The output impedances are then translated into frequency thus allowing the realization of broadband power amplifiers (PAs) at high-power level of 30 W. In this work, the Class-ABJ broadband approach will be used for the realization of a reconfigurable dual-band power amplifier operating in the two frequency bands 2.1–2.2 and 2.5–2.6 GHz. Continuous wave (CW) measurements on the realized PA show power and efficiency greater than 17 W and 55% in the two frequency bands with peak values up to 30 W and 63.7%. Indeed, it is shown that such novel modes can be predistorted and therefore the linearity requirement can also be met.